MicroRNA-138 enhances TRAIL-induced apoptosis through interferon-stimulated gene 15 downregulation in hepatocellular carcinoma cells - Chaohui Zuo; Xinyi Sheng; Zhuo Liu; Min Ma; Shuhan Xiong; Hongyu Deng; Sha Li; Darong Yang; Xiaohong Wang; Hua Xiao; Hu Quan; Man Xia (Tumor Biology, 2017)
Hepatocellular carcinoma is a leading cause of cancer-related mortality worldwide. TRAIL (tumor necrosis factor–related apoptosis–inducing ligand) is a potential target for cancer therapy. However, many cancer cells are resistant to TRAIL-induced apoptosis and its mechanism is not well understood. In this study, to identify potential therapeutic targets for TRAIL-resistant cancer cells, we compared the expression levels of interferon-stimulated gene 15 in TRAIL-sensitive and TRAIL-resistant hepatocellular carcinoma cell lines. Western blot analysis showed that interferon-stimulated gene 15 expression levels were significantly higher in resistant HLCZ01and Huh7 cells than in sensitive LH86 and SMMC-7721 cells. Interferon-stimulated gene 15 knockdown in resistance cells led to TRAIL sensitivity. Conversely, interferon-stimulated gene 15 overexpression in sensitive cells resulted in TRAIL resistance. Our bioinformatics search detected a putative target sequence for microRNA miR-138 in the 3′ untranslated region of the interferon-stimulated gene 15. Real-time quantitative polymerase chain reaction analysis demonstrated that miR-138 was significantly downregulated in TRAIL-resistant cells compared to TRAIL-sensitive cells. Forced expression of miR-138 in resistant cells decreased both messenger RNA and protein levels of interferon-stimulated gene 15, and when exposed to TRAIL, activated poly(adenosine diphosphate-ribose) polymerase, indicating sensitization to TRAIL. The results suggested that miR-138 regulates the interferon-stimulated gene 15 expression by directly targeting the 3′ untranslated region of interferon-stimulated gene 15 and modulates the sensitivity to TRAIL-induced apoptosis. MiR-138 may be a target for therapeutic intervention in TRAIL-based drug treatments of resistant hepatocellular carcinoma or could be a biomarker to select patients who may benefit from the treatment.